F. H. Bradley entre orthodoxie et hérésie : le sens des ‘Concluding Remarks’ de Ethical Studies - Jean-Paul Rosaye (Revue Française de Civilisation Britannique, 2013)
F. H. Bradley’s ‘Concluding Remarks’, ending his Ethical Studies (1876), were undeniably significant in prompting his subsequent metaphysical work. Yet, they have rarely been studied as a separate text, despite its fame among the members of the London Ethical Society in late-Victorian times. In this text, Bradley’s answer to the threat of materialism and agnosticism endangering true faith and orthodoxy shaped a very ambiguous religious solution to ethics. While consolidating the concept of self-realization he had contributed to define against utilitarian and Kantian presuppositions, his views suggested an interpretation of faith wavering between an orthodox statement and some heretical positions which could satisfy but a small number of religious believers.